SISTEM INFORMASI NILAI MAHASISWA BERBASIS SMS GATEWAY PADA FAKULTAS PERTANIAN UNIVERSITAS BENGKULU - Meiyanto Heri Prasetyo; Asnawati Asnawati; Yode Arliando (Jurnal Media Infotama, 2015)
This study aims to develop a system of SMS gateway, knowing functionality, usability and performance of the SMS gateway in the view students. Half the value of information announcements are usually made conventional. It is considered to be ineffective and inefficient to meet the needs of students. The procedure of this study using the method in the process SMS-based web application design using stages in the System Development Life Cycle (SDLC), namely the stages of analysis, design, implementation, and testing. The tests were conducted to analyze the quality of software functionality, usability, and efficiency. Function test results that have been made for all applications web and SMS functions in accordance with sub-characteristics functionality. The results of usability testing is an application designed for 88.75 % and included in the excellent category. The results of testing the efficiency of the process auto reply SMS to ask for the data is 3.26 minutes / SMS. This system is efficient in terms of time to obtain information on the value of students every semester.Keyword: SMS Gateway, Gammu